1997
DOI: 10.1017/s0022215100137375
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillar metastasis from a renal cell carcinoma presenting as a quinsy

Abstract: We present a rare case of renal cell carcinoma metastatic to the tonsil. Tonsillectomy was inadvertently performed during an attempt to drain what was clinically a peritonsillar abscess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In agreement with other researchers, the possibility of PTA as an independent risk factor for tonsillar malignancy was questioned [1,3,10]. A literature search revealed several case reports on tonsillar malignancy presenting as PTA, which supported the concept that PTA may be associated with tonsillar malignancy [5][6][7][8][9][10][12][13][14]. Thus, clarification of whether PTA should be added to the list of risk factors indicating histological examination is warranted.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…In agreement with other researchers, the possibility of PTA as an independent risk factor for tonsillar malignancy was questioned [1,3,10]. A literature search revealed several case reports on tonsillar malignancy presenting as PTA, which supported the concept that PTA may be associated with tonsillar malignancy [5][6][7][8][9][10][12][13][14]. Thus, clarification of whether PTA should be added to the list of risk factors indicating histological examination is warranted.…”
Section: Introductionsupporting
confidence: 69%
“…In seven cases (54 %), malignancy was unsuspected. If the previously mentioned risk factors for tonsillar malignancy had been applied, some of these malignancies would have been suspected; the patient described by Green et al (Table 3, case number 3) had a history of cancer and the second case reported by Holmes et al (Table 3, case number 6) was immunocompromised due to HIV [6,7]. Both conditions are included in the list of risk factors for tonsillar malignancy indicating histological examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Older patients presenting with peritonsillar abscesses may require further assessment to detect OPC. [5][6][7] It is impossible to say if patients' prognoses were affected by delayed diagnosis. However, earlier-stage OPC has a better prognosis than advanced stage and the nonresolving nature of the symptoms in these patients were suggestive of malignancy.…”
Section: Methodsmentioning
confidence: 99%